Expression of matrix metalloproteinases 1, 2, 9, 12 in xenogenic tissues of epoxy-crosslinked bioprosthetic heart valves explanted due to dysfunction - A. E. Kostyunin; T. V. Glushkova (Российский кардиологический журнал, 2020)
Aim. To study the expression patterns of matrix metalloproteinases (MMPs) -1, -2, -9, -12 in the leaflets of the epoxy-treated bioprostheses explanted due to dysfunction and to identify the pathways for the accumulation of these enzymes in the xenogenic tissues.Methods. 19 leaflets from seven epoxy-treated bioprostheses (Kemcor (n = 2), PeriCor (n = 2), UniLine (n = 2) and TiAra (n = 1)) explanted from the mitral or aortic positions during repeat heart valve replacements were included in a study. Sections for microscopic studies were cut on a standard rotary microtome. Cell typing and the expression of MMP-1, -2, -9, -12 were evaluated using immunohistochemical staining with the antibodies against PTPRC/CD45, CD68, neutrophil myeloperoxidase and the corresponding MMPs. Stained samples were examined by light microscopy.Results. Sporadic cell infiltrates, mainly composed of macrophages (PTPRC/CD45+, CD68+), were found in 17 leaflets from six explanted bioprostheses. Positive staining for MMP-1, -2, -9, -12 was colocalized with immune cell infiltrates. It is worth noting that MMP-9 staining was visualized even in the absence of cell infiltration, while more intense staining was found in the areas with a loose extracellular matrix. There were no signs of macrophage infiltration or MMP expression in xenotissues of pericardial bioprostheses failed due to thrombosis and explanted two days after implantation. However, a blood clot formed on its surface showed intense MMP-9 staining and included a large proportion of neutrophils positive for myeloperoxidase.Conclusion. Macrophages and other immune cells that infiltrate xenotissues of epoxy-treated bioprostheses are sources of MMP-1, -2, -9, -12. In addition, MMP-9 can diffuse into bioprosthetic valve leaflets from blood plasma of patients. Thus, MMPs deposition in xenotissues may contribute to the leaflet ruptures and calcifications leading to the development of bioprosthetic valve dysfunction.